Erratum: Effects of chirality and inhomogeneous growth on the morphology of plant tendril. (1st February 2023) - Zhao, Hui-Chuan; Bian, Li-Chun; Zhang, Tao; Dong, Jia-Jun
Abstract: Original article: EPL, 136 (2021) 48004 .